Oral Health Care An Important Issue of the Modern Society - Cosmina Ardelean, Lavinia; Cristina Rusu, Laura (Dentistry, 2022)
Oral health care is an issue of modern society that is sometimes difficult to manage. Considered a key indicator of global health, well-being, and quality of life, oral health's relationship with general health is of utmost importance. As such, maintenance of oral health should be a lifelong commitment as well as a daily priority. This book includes twenty chapters that focus on different aspects of oral health issues, including prevention, treatment, and management.